PENGARUH FREKUENSI PIJAT BAYI TERHADAP PERTUMBUHAN (BERAT BADAN) BAYI USIA 1-3 BULAN DI DESA KARANGSARI DAN PURBADANA - Sugiharti, Rosi Kurnia (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
ABSTRACT: EFFECT OF FREQUENCY ON GROWTH OF INFANT MASSAGE (WEIGHT) INFANTS AGE 1-3 MONTHS VILLAGE KARANGSARI AND PURBADANA. Infancy is a golden age once the critical period of growth and development. Achieving optimal growth and development is the result of the interaction of a variety of interrelated factors, namely genetics, environment and behavior, as well as stimulation or stimulation useful. Objective: this study to determine the effect of the frequency of infant massage on the growth of infants aged 1-3 months in the village Karangsari and Purbadana. This type of research: a quasi experimental approach to non randomized pretest posttet with control group design and sampling techniques with purposive sampling. Samples are infants aged 1-3 months were 30 infants consisted of 10 infants as control group, 10 infants as massage intervention group 1x / day and 10 infants as massage intervention group 2x / day. Analysis of differences in growth (weight) using paired T test. For the analysis of the frequency of infant massage effect on the growth (weight) using One Way Anova Test. Result: The study obtained no difference in growth (weight) before and after the intervention in all three groups (p = 0.0001 <Î±0.05). Test results of the analysis with One Way Anova mention no frequency effect of infant massage on the growth (weight) Keywords: Frequency of infant massage, GrowthÂ